The Problem of Sports Betting in Kenya: Striking a Balance between Private Profit and Public Good - Gitau, Victoria (Strathmore Law Review, 2018)
The inception of sports betting in Kenya has brought forth great excitement to prospective bettors and shrewd betting operators which has resulted in an equal amount of controversy and muddle. This note seeks to address the conflict between the private profit that investors and the economy reap, and the public good that the state owes its citizens by virtue of its fiduciary duty over its people. The author scrutinises the current law of sports betting in Kenya to demonstrate that it is not sufficient to speak to the two conflicting issues and that a concession is possible.